EVALUASI KEBIJAKAN DIGITALISASI ADMINISTRASI PUBLIK MELALUI PENDEKATAN HUMAN-CENTERED GOVERNANCE DI KABUPATEN MINAHASA - Rantung, Margareth Inof Riisyie; Abdussamad , Zuchri; Alhasni , Rahma A. (Sawala : Jurnal Administrasi Negara, 2025)
Digital transformation in public administration is a crucial part of bureaucratic reform in Indonesia. However, the effectiveness of digital public administration implementation in Minahasa Regency faces obstacles such as low digital literacy, limited infrastructure, inadequate civil service capacity, and minimal community involvement. This study aims to evaluate the implementation of digitalization policies using a human-centered governance approach through the CIPP evaluation model. This research employs a descriptive qualitative method through interviews, observations, and document studies. The results indicate that digitalization needs have not fully considered the social-geographical conditions, infrastructure and HR limitations hinder implementation, the digital service socialization process is suboptimal, and the digital services provided have not fully improved public satisfaction. This study emphasizes that a human-centered governance approach is essential to enhancing the effectiveness of local digital services. The findings contribute to integrating the real needs of citizens into the planning, implementation, and evaluation of public administration digitalization policies.